Visual and Spatial Working Memory Abilities Predict Early Math Skills: A Longitudinal Study - Fanari, Rachele; Meloni, Carla; Massidda, Davide (Frontiers in Psychology, 2019)
This study aimed to explore the influence of the visuospatial active working memory sub-components on early math skills in young children, followed longitudinally along the first two years of primary school. We administered tests investigating visual active working memory (jigsaw puzzle), spatial active working memory (backward Corsi), and math tasks to 43 children at the beginning of first grade (T1), at the end of first grade (T2), and at the end of second grade (T3). Math tasks were select according to the children’s age and their levels of formal education: the “Battery for the evaluation of numerical intelligence from 4 to 6 years of age” (BIN 4–6) at T1 to test early numerical competence and the “Test for the evaluation of calculating and problem-solving abilities” (AC-MT 6–11) to test math skills at T2 and T3. Three regression models, in which the predictors were identified through a forward selection based on the use of the Bayesian information criterion (BIC) index, were performed to study the relationship between visual and spatial working memory and math ability at the three points in time. The results show that spatial working memory influences early numerical performance at T1, while early numerical performance is the unique predic-tor of math performance at T2. At the end of the second grade, the regression model reveals a relationship between math performance and both visual and spatial working memory and the attenuation of the importance of domain-specific predictors. The study depicts the dif-ferent implications of visual and spatial working memory predictors over the children’s de-velopment periods and brings additional evidence to the debate on the relationship between visuospatial working memory and math ability in young children.